Theory of mind in women with borderline personality disorder or schizophrenia: differences in overall ability and error patterns - Vaskinn, Anja; Antonsen, Bjørnar T.; Fretland, Ragnhild A.; Dziobek, Isabel; Sundet, Kjetil; Wilberg, Theresa (Frontiers in Psychology, 2015)
Although borderline personality disorder (BPD) and schizophrenia (SZ) are notably different mental disorders, they share problems in social cognition—or understanding the feelings, intentions and thoughts of other people. To date no studies have directly compared the social cognitive abilities of individuals with these two disorders. In this study, the social cognitive subdomain theory of mind was investigated in women with BPD (n = 25), women with SZ (n = 25) and healthy women (n = 25). An ecologically valid video-based measure (Movie for the Assessment of Social Cognition) was used. For the overall score, women with SZ performed markedly below both healthy women and women with BPD, whereas women with BPD did not perform significantly different compared to the healthy control group. A statistically significant error type × group interaction effect indicated that the groups differed with respect to kind of errors. Whereas women with BPD made mostly overmentalizing errors, women with SZ in addition committed undermentalizing errors. Our study suggests different magnitude and pattern of social cognitive problems in BPD and SZ.